Results of Studying Selected Functional Indicators in Schoolchildren - Umirzoqov Eldor Ochil o‘g‘li; Buranova Gulnoza Boymuratovna (American Journal of Biodiversity, 2026)
The article presents comparative characteristics of body weight, height, chest circumference, and Ketle index of boys and girls aged 11- 18 years in the city of Karshi. According to the results, no differences were found in body weight, height, and Ketle index in all age groups of students.